2014
DOI: 10.1007/s12032-014-0325-9
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center randomized phase II clinical study of bevacizumab plus irinotecan, 5-fluorouracil, and leucovorin (FOLFIRI) compared with FOLFIRI alone as second-line treatment for Chinese patients with metastatic colorectal cancer

Abstract: Bevacizumab is an anti-VEGF human monoclonal antibody suitable for chemotherapy for patients with metastatic colorectal cancer (mCRC). This study investigated the efficacy and safety of using bevacizumab plus irinotecan, 5-fluorouracil, and leucovorin (FOLFIRI) as second-line chemotherapy option for patients with mCRC in China. Patients with mCRC, who had been previously treated with oxaliplatin-based chemotherapy, but not bevacizumab, were randomly assigned to two groups to receive bevacizumab plus FOLFIRI (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 14 publications
0
31
1
Order By: Relevance
“…A total of 7,571 patients were enrolled in these trials, and the median number of enrolled patients was 197 (range, 75 to 1,226). The primary endpoint was PFS in 12 trials (60%) [11-15,18,19, 21-24,30], OS in six trials (30%) [16,20,26-29] and ORR in one trial (5%) [17]. In one trial (5%), PFS and OS were co-primary endpoints [25].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 7,571 patients were enrolled in these trials, and the median number of enrolled patients was 197 (range, 75 to 1,226). The primary endpoint was PFS in 12 trials (60%) [11-15,18,19, 21-24,30], OS in six trials (30%) [16,20,26-29] and ORR in one trial (5%) [17]. In one trial (5%), PFS and OS were co-primary endpoints [25].…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] VEGF and its receptors are frequently overexpressed in human tumors and inhibition of angiogenesis with bevacizumab, a monoclonal antibody that selectively binds to VEGF has shown promising clinical efficacy. [20][21][22][23][24] Multiple studies have shown that high VEGF expression in tumor or in serum is an indicator of prognosis of non-small cell lung cancer and response to anti-angiogenesis. 25,26 As such, VEGF SNP has been extensively investigated for its role in predicting cancer susceptibility, progression and anti-VEGF therapeutic response in subjects with tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse outcomes associated with late diagnosis in most patients are due to distant metastasis, lymphatic dissemination and recurrence . The combination of cytotoxic chemotherapy and targeted drugs has improved the overall survival (OS) of patients with advanced CRC by nearly 30 months . However, the systemic outcomes in some patients have been unsatisfactory and, in addition to the adverse effects of chemotherapy, have considerably reduced their quality of life .…”
Section: Introductionmentioning
confidence: 99%